Reversal of valproate-induced major salivary gland changes by moringa oleifera extract in rats - YARAT, AYŞEN (My University, 2024)
This study aimed to explore the potential protective impacts ofMoringa oleiferaextract on major alteration in salivary glands of rats exposed to sodium valproate (VA). Groups were defined as control, control+moringa extract, sodium valproate, and sodium valproate+moringa extract. Antioxidant and oxidant status, activities of digestive and metabolic enzymes were examined. VA treatment led to various biochemical changes in the salivary glands, including decreased levels of antioxidants like glutathione, glutathione-S-transferase, and superoxide dismutase (except for sublingual superoxide dismutase). Conversely, a decrease in alpha-amylase, alkaline and acid phosphatase, lactate dehydrogenase, protease, and maltase activities were observed. The study also demonstrated that VA induces oxidative stress, increases lipid peroxidation, sialic acid, and nitric oxide levels in the salivary glands. Total oxidant capacity was raised in all glands except in the sublingual gland. The electrophoretic patterns of proteins were similar.Moringa oleiferaextract exhibited protective properties, reversing these VA-induced biochemical changes due to its antioxidant and therapeutic attributes. This research suggests that moringa extract might serve as an alternative treatment approach for individuals using VA and experiencing salivary gland issues, although further research is necessary to confirm these findings in human subjects.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)